Reforma al libro ii, título iii, del código de la niñez y adolescencia, sobre la situación de tenencia de los menores de edad por causa de la separación o divorcio de los padres - Ordóñez Díaz, Rommel Santiago (2016)
The rule contained in Article 69, paragraph 5 of the Constitution of the Republic of Ecuador stipulates that the State shall protect parents and householders, in the exercise of their duties. It will promote paternal and maternal responsibility and monitor the implementation of the reciprocal rights and duties between parents and children. However within the Code of Children and Adolescents in Book II, Title III, Tenure; not the responsibility of the parents in case of divorce is regulated, since only sole custody is recognized, it is for this reason that constitutional law recognizes joint custody as the most suitable mechanism causing less impact on the children in cases of separation or divorce of their parents. Faced with the problem described above I decided to prepare this research work entitled "REFORM Book II, Title III, CODE OF CHILDREN AND YOUTH ON THE STATUS OF HOLDINGS OF MINORS BECAUSE OF SEPARATION OR DIVORCE OF PARENTS "I perform in a doctrinaire analysis custody, therefore in this work the theoretical arguments, results of field research, in which analysis demonstrated the need to establish a mechanism to implement joint custody, being the main idea of my thesis, collected with I hope it will help to solve this problem.